1993
DOI: 10.2466/pms.1993.76.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Attributions (Beliefs) and Job Satisfaction Associated with Back Pain in an Industrial Setting

Abstract: We investigated possible differences between management and workers in attributions about the cause and prevention of industrial back pain. 145 employees from upper management, lower management, and blue-collar ranks completed several questionnaires. Age, sex, job satisfaction, and history of back pain were also examined for possible confounding effects. There were significant differences in attributions between job levels, with upper management believing more strongly in causal factors related to the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Although driving vehicles by itself is considered to be a risk factor for the occurrence of back pain because of body vibration (Johanning, 1991;Burdorf et al, 1993), it could be that in this cohort of workers the time riding a forklift truck is a surrogate for the amount of time not performing heavy physical tasks and is therefore a protective factor for the incidence of back pain. The relationship between low job satisfaction and back pain has been reported earlier in both cross-sectional studies (Holmström et al, 1993;Linton and Warg, 1993;Symonds et al, 1996) and longitudinal studies (Bigos et al, 1991(Bigos et al, , 1992 in industrial settings. In general populations results have been less consistent: a cross-sectional study reported an association between low job satisfaction and back pain among women (Svensson and Andersson, 1989), whereas a longitudinal study found no association in a general population of men and women (Biering-Sørensen and Thomsen, 1986).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Although driving vehicles by itself is considered to be a risk factor for the occurrence of back pain because of body vibration (Johanning, 1991;Burdorf et al, 1993), it could be that in this cohort of workers the time riding a forklift truck is a surrogate for the amount of time not performing heavy physical tasks and is therefore a protective factor for the incidence of back pain. The relationship between low job satisfaction and back pain has been reported earlier in both cross-sectional studies (Holmström et al, 1993;Linton and Warg, 1993;Symonds et al, 1996) and longitudinal studies (Bigos et al, 1991(Bigos et al, , 1992 in industrial settings. In general populations results have been less consistent: a cross-sectional study reported an association between low job satisfaction and back pain among women (Svensson and Andersson, 1989), whereas a longitudinal study found no association in a general population of men and women (Biering-Sørensen and Thomsen, 1986).…”
Section: Discussionmentioning
confidence: 55%
“…These findings implicate that interventions aimed at increasing job satisfaction, changing beliefs on (causes of) back pain, and encouraging a positive attitude towards back pain may be effective in the prevention of back pain. Previous studies on beliefs of workers concerning back pain showed that both the attribution of back pain to work-related causes and opinions on preventive measures were dependent on the history of back pain and were different between clerical and manual workers (Linton and Warg, 1993;Hyytiäinen, 1994). Since an intervention should correspond with the beliefs and needs of the workers, it may be wise to assess the workers' beliefs regarding causes and prevention of back pain, and general measures for improving the work situation before designing and implementing an intervention.…”
Section: Discussionmentioning
confidence: 98%
“…The perceived risk that current pain might become persistent, and how likely it is that the person would be working within 6 months were assessed by two items rated on a scale from 1 to 10 with 1 = ‘no chance’ and 10 = ‘very high chance’. A single item assessed work satisfaction: ‘If you take into consideration your work routines, management, salary, promotion possibilities, and workmates, how satisfied are you with your job?’ Ratings were made on a 1–10 point scale, with ‘not at all satisfied’ and ‘completely satisfied’ as endpoints (33).…”
mentioning
confidence: 99%
“…Another interesting outcome of this study was the lack of relationship between job satisfaction prior to the injury and the measures of medical outcomes. We initially decided to investigate the relationship between these variables because some evidence existed that job satisfaction predicts work place injuries [Bigos et al, 1991;Linton & Warg, 1993;Melamed et al, 1992]. For example, in Bigos et al's study subjects who stated that they ''hardly ever'' enjoyed their job tasks were 2.5 times more likely to report a back injury than were those who reported that they ''almost always'' enjoyed their job tasks.…”
Section: Discussionmentioning
confidence: 99%